IMPLEMENTASI KEBIJAKAN TATA KELOLA BARANG MILIK DAERAH DALAM MENDUKUNG KINERJA BADAN PENGELOLAAN KEUANGAN DAN ASET DAERAH KOTA CIMAHI - sofyan Sofyan; Deden Hadi Kushendar; Betty Wargadinata (FISIP Universitas Muhammadiyah Sidenreng Rappang, 2023)
This study aims to find out how the implementation of regional property management in supporting the performance of the Cimahi City Regional Financial and Asset Management Agency. The research conducted by the author uses qualitative research methods, using primary data sourced from interviews with selected informants using the purposive sampling method, while secondary data is obtained from official documents used such as interview results, field notes or documentation. other. The data collection techniques used in this study are observation techniques, interview techniques and documentation techniques. The results of this study indicate that the implementation of regional property management in supporting the performance of the Cimahi City Regional Financial and Asset Management Agency has not been optimally implemented according to policy. This is indicated by the Cimahi City BPKAD staff still adapting to the new regulation, namely the Regional Regulation on the management of regional property No. 4 years 2021